2010
DOI: 10.1155/2010/153273
|View full text |Cite
|
Sign up to set email alerts
|

Structural Health Monitoring in Changing Operational Conditions Using Tranmissibility Measurements

Abstract: Abstract. This article uses frequency domain transmissibility functions for detecting and locating damage in operational conditions. In recent articles numerical and experimental examples were presented and the possibility to use the transmissibility concept for damage detection seemed quite promising. In the work discussed so far, it was assumed that the operational conditions were constant, the structure was excited by a single input in a fixed location. Transmissibility functions, defined as a simple ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 8 publications
0
8
0
1
Order By: Relevance
“…However, in the literature [15], [21], it has been pointed that several important issues, such as the frequency range and the location of input, have to be considered first. In this section, detailed discussions on these issues are given as below.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the literature [15], [21], it has been pointed that several important issues, such as the frequency range and the location of input, have to be considered first. In this section, detailed discussions on these issues are given as below.…”
Section: Discussionmentioning
confidence: 99%
“…A carefully chosen frequency range can improve the detection accuracy. In [21], it has been shown that damage in a cantilever beam can be more accurately detected using a small frequency band around resonance frequencies of the structure than that using the whole frequency range. However, in many practical applications, it is hard to determine a specific frequency band without knowing the frequency responses of all possible damage or faults.…”
Section: Discussionmentioning
confidence: 99%
“…Other recent studies have applied the transmissibility to the problem of transfer path analysis in vibro-acoustics (Tcherniak & Schuhmacher, 2009) and for damage detection (Canales et al, 2009;Devriendt, Vanbrabant, et al, 2009;Urgueira et al, 2011).…”
Section: Other Applicationsmentioning
confidence: 99%
“…As an alternative, transmissibility measurements have been widely explored as features in damage detection for SHM [9]- [12], due to their output-only nature [13]- [15], which implies the need for measuring only the response signals, without any knowledge about the excitation forces.…”
Section: Introductionmentioning
confidence: 99%